Synthesis and biological activity of (theobromine-1-yl)acetic acid benzyliden hydrazides - Ivanchenko, D. G.; Varahabhatla, S. C. R. V.; Іванченко, Дмитро Григорович (Запорізький державний медичний університет, 2015)
Key way for creating new medicinal drugs is structural modification of known and existent natural compounds with high biological activity. In this aspect researchers’ attention is drawn by xanthine derivatives which appear to be antagonists of adenosine receptors, phosphodiesterase inhibitors and histone deacetylase inducers. This resulted in their widespread application in medicine as diuretics, analgesics, heart pacemakers, anti-inflammatory, psychotropic and renal protective agents.
Keywords: тези